Electrostatic adsorption structure based on laminated concentric circle configuration and process method thereof
Patent Information
- Application Number
- CN202610222728.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2026-02-25
- Publication Date
- 2026-10-30
- Estimated Expiration
- 2046-02-25
AI Technical Summary
[0007]针对现有静电吸附技术中存在的上述缺陷,本发明旨在提供一种基于叠层同心圆构型的静电吸附结构及其工艺方法,以解决以下技术问题:1、克服传统平面静电吸附膜吸附力不足和稳定性不高的缺陷,实现更大的平均吸附力和更小的吸附力波动,从而提升吸附力与稳定性;2、弥补刚性静电卡盘和现有柔性静电吸附结构无法有效吸附表面粗糙度较大以及表面曲率较大的吸附面的缺陷,实现对复杂表面的自适应吸附;3、通过优化电极的构型和参数,实现静电吸附力的最大化,同时避免电极间距过小导致的击穿风险;4、增强环境适应性,提高静电吸附结构在高低温、辐射、等离子体等恶劣环境下的适应性和可靠性,满足航天器在轨操作等特殊场景的需求;本发明通过采用叠层同心圆构型的电极设计、柔性材料的选择以及合理的结构参数优化,成功解决了上述技术问题,弥补现有方向的空白,为静电吸附技术在更广泛领域的应用提供了有力的技术支撑
1、本发明通过采用叠层同心圆电极构型及8:7最优电极宽距比,突破了传统平面静电吸附结构的性能瓶颈。实验数据表明,在相同激励电压与吸附面积条件下,本发明的平均吸附力较商用静电卡盘及传统平面静电吸附膜均有显著提升,吸附力稳定性也得到大幅增强。这一性能突破有效解决了传统结构在精密加工、在轨操作等场景中易出现的工件位移、吸附失效问题,为高端制造与航天任务提供了可靠的技术支撑。
Smart Images

Figure CN121716376B_ABST
Abstract
Description
Technical Field
[0001] This application relates to the field of electrostatic adsorption technology, and in particular to an electrostatic adsorption structure based on a stacked concentric circle configuration and its manufacturing process. Background Technology
[0002] On-orbit operation technology is a core cornerstone supporting the sustainable and efficient development of space activities, and is of great significance. This technology can extend the service life of expensive space assets, enhance mission resilience and reliability, and enable the efficient operation of missions such as large space stations and deep space exploration through refueling, modular assembly, orbital correction, fault repair, and equipment replacement. At the same time, on-orbit operation technology can effectively mitigate space debris problems, reduce the cost of space activities, and has irreplaceable strategic value for space safety and the development of the aerospace industry.
[0003] The approach and attachment of a servicing spacecraft to a target spacecraft is a prerequisite for on-orbit operations. Currently, commonly used adsorption technologies include negative pressure adsorption, magnetic adsorption, adhesive bonding, and biomimetic dry bonding. However, these technologies all have significant drawbacks in the space environment: traditional negative pressure adsorption relies on the atmospheric pressure difference to generate adsorption force, which fails directly in the vacuum environment of space and cannot meet the requirements of on-orbit operations; magnetic adsorption is only applicable to target spacecraft made of ferromagnetic materials and is ineffective for target spacecraft made of non-magnetic materials, and there is a risk of interfering with precision instruments and potential demagnetization; adhesive bonding has problems such as difficulty in curing, low precision tolerance, and irreversibility in the low-temperature vacuum environment, making it difficult to achieve dynamically controllable adsorption and desorption; biomimetic dry bonding is susceptible to space dust contamination and radiation embrittlement, which damages its microstructure, and has extremely stringent requirements for the flatness and cleanliness of the target surface, thus limiting its applicability.
[0004] Electrostatic adsorption technology works by energizing the electrodes in an electrostatic adsorption structure. Due to electrostatic induction, an opposite charge is induced on the surface of the object to be adsorbed, generating an electrostatic force between the structure and the object for adsorption. This technology has unique advantages in a vacuum environment, is applicable to both conductive and insulating materials, and enables dynamically controllable adsorption. The adsorption and desorption process can be triggered instantly by switching the power on and off, and the adsorption force can be precisely adjusted by the excitation voltage to meet diverse load requirements. It does not require high surface flatness of the adsorbed object, can operate reliably under conditions of considerable roughness, and can be extended to the stable adhesion of large planar structures.
[0005] Currently, the core application of electrostatic adsorption technology is focused on electrostatic chucks in semiconductor manufacturing. In precision processing such as wafer lithography and chemical vapor deposition, electrostatic chucks achieve micron-level stable clamping of wafers through voltage excitation, releasing them instantaneously upon power failure. This technology solves the risks of particulate contamination and stress damage associated with traditional mechanical clamps, while simultaneously meeting the stringent requirements of both ultra-clean environments and nanoscale process precision. However, precision semiconductor manufacturing requires electrostatic chucks to use high-rigidity insulating materials such as alumina or aluminum nitride ceramics to ensure wafer flatness. This means that rigid electrostatic chucks cannot effectively adsorb onto surfaces with large surface roughness, becoming a key bottleneck restricting its application in a wider range of fields.
[0006] To overcome the shortcomings of rigid electrostatic chucks, a flexible electrostatic adsorption structure has emerged in the prior art. For example, patent CN202310995919.8 discloses a film-based composite electrostatic adsorption device. This device combines electrostatic adsorption technology with adhesive adsorption technology, achieving reliable bonding during the process and detachment after the task is completed. However, the electrostatic adsorption layer of this device is bonded to a rigid backing plate in a planar parallel configuration, resulting in severe attenuation of the edge electric field. This makes it unable to effectively adapt to adsorption surfaces with large surface roughness and curvature, and thus difficult to meet the needs of complex scenarios such as on-orbit operation of spacecraft. In addition, traditional planar electrostatic adsorption films also suffer from insufficient adsorption force and low stability, which can easily lead to wafer or workpiece displacement and decreased processing accuracy during processing, becoming one of the key bottlenecks restricting the yield and efficiency of high-end processes. Summary of the Invention
[0007] To address the aforementioned shortcomings of existing electrostatic adsorption technologies, this invention aims to provide an electrostatic adsorption structure and its manufacturing process based on a layered concentric circle configuration, thereby solving the following technical problems: 1. Overcoming the deficiencies of insufficient adsorption force and low stability in traditional planar electrostatic adsorption films, achieving a larger average adsorption force and smaller adsorption force fluctuations, thus improving adsorption force and stability; 2. Compensating for the inability of rigid electrostatic chucks and existing flexible electrostatic adsorption structures to effectively adsorb adsorption surfaces with large surface roughness and curvature, achieving adaptive adsorption for complex surfaces; 3. Maximizing electrostatic adsorption force by optimizing electrode configuration and parameters, while avoiding the risk of breakdown caused by excessively small electrode spacing; 4. Enhancing environmental adaptability, improving the adaptability and reliability of the electrostatic adsorption structure in harsh environments such as high and low temperatures, radiation, and plasma, meeting the needs of special scenarios such as on-orbit operation of spacecraft; This invention, through the adoption of a layered concentric circle configuration electrode design, the selection of flexible materials, and reasonable structural parameter optimization, successfully solves the above-mentioned technical problems, fills the gap in existing directions, and provides strong technical support for the application of electrostatic adsorption technology in a wider range of fields.
[0008] This application provides an electrostatic adsorption structure based on a stacked concentric circle configuration, employing the following technical solution: An electrostatic adsorption structure based on a stacked concentric circle configuration includes, from bottom to top, a flexible connecting base plate, a flexible base layer, a second electrode layer, a flexible intermediate layer, a first electrode layer, and a flexible insulating layer. Each layer is fixedly connected by hot pressing or bonding. The flexible insulating layer serves as the adsorption contact surface of the electrostatic adsorption structure. The second electrode layer is a solid circular electrode, and the first electrode layer is a concentric circular electrode. The ratio of the electrode width to the spacing of the first electrode layer is 8:7. The first electrode layer and the second electrode layer are respectively connected to excitation voltages of opposite polarities to generate electrostatic adsorption force between the electrostatic adsorption structure and the adsorbed object.
[0009] Furthermore, the materials of the flexible insulating layer, flexible intermediate layer, and flexible base layer are polyimide (PI), polyethylene terephthalate (PET), polyvinylidene fluoride (PVDF), polyethylene naphthalate (PEN), polyphenylene sulfide (PPS), polycarbonate (PC), polyurethane (PU), parylene (Parylene), silicone, biaxially oriented polypropylene (BOPP), and other polymer film materials, as well as one or more of PDMS, ECOFLEX0030, and ECOFLEX0050 insulating silicone rubber.
[0010] Furthermore, the thickness of the flexible insulating layer is 5-30 μm, the thickness of the flexible intermediate layer is 10-50 μm, and the thickness of the flexible base layer is 10-100 μm.
[0011] Furthermore, the materials of the first electrode layer and the second electrode layer are one or more of copper, silver, conductive ink, or carbon nanotube conductor materials.
[0012] Furthermore, the thickness of the first electrode layer is 5-20 μm, and the thickness of the second electrode layer is 5-20 μm.
[0013] Furthermore, the flexible connecting base plate is made of one or more of polyimide, polyetheretherketone, polytetrafluoroethylene, or silicone rubber. The flexible connecting base plate has a compressive strength of <50kPa and an elongation at break of >10% to improve the contact between the electrostatic adsorption structure and the target object, thereby enhancing the electrostatic adsorption force. It also has good insulation properties and can adapt to high and low temperature, radiation, and plasma environments.
[0014] Furthermore, the excitation voltage can be DC, sine wave, square wave, or any waveform.
[0015] Furthermore, the electrode width of the first electrode layer is 0.3-2 mm, and the electrode spacing is 0.15-1.75 mm.
[0016] Furthermore, a method for fabricating an electrostatic adsorption structure based on a stacked concentric circle configuration is also provided, comprising the following steps: S1: A flexible substrate consisting of a flexible insulating material as a flexible intermediate layer, a laminate with double-sided conductive material as the first electrode layer and the second electrode layer, and the three layers forming a substrate. S2: Negative dry films are laminated on both sides of the substrate simultaneously. The upper dry film is irradiated with ultraviolet light through a concentric circle mask pattern with an electrode width to spacing ratio of 8:7 and the lower dry film is irradiated with a solid circle mask pattern. The dry film in the irradiated area hardens to form an insoluble resist layer. S3: Use a developer to remove the dry film from the unexposed areas, and then use an etchant to etch away the copper layer that is not protected by the dry film, thereby forming the designed electrode pattern. S4: Use 3% NaOH sodium hydroxide solution to peel off the remaining hardened dry film, exposing the completed flexible circuit, to obtain the upper concentric circle first electrode layer and the lower solid circle second electrode layer; S5: Under hot pressing conditions of 150-200℃ and 2.0-3.0MPa, the two cover layers, flexible insulating layer and flexible base layer, are laminated to both sides of the etched substrate for 2-4 hours to ensure a tight bond between the cover layer and the electrode layer and to eliminate interlayer bubbles. Each cover layer also includes a thermal adhesive layer. S6: The prepared structure is attached to the flexible connecting base plate, and the first electrode layer and the second electrode layer are connected to excitation voltages of opposite polarities respectively. The vertical stacking design of concentric circular electrodes and solid circular electrodes forms a longitudinal electric field superposition, which enhances the adsorption force and obtains an electrostatic adsorption structure based on the stacked concentric circular configuration.
[0017] In summary, this application includes at least one of the following beneficial technical effects: 1. This invention overcomes the performance bottleneck of traditional planar electrostatic adsorption structures by employing a stacked concentric circle electrode configuration and an optimal 8:7 electrode width-to-spacing ratio. Experimental data shows that, under the same excitation voltage and adsorption area, the average adsorption force of this invention is significantly improved compared to commercial electrostatic chucks and traditional planar electrostatic adsorption films, and the stability of the adsorption force is also greatly enhanced. This performance breakthrough effectively solves the problems of workpiece displacement and adsorption failure that easily occur in traditional structures in precision machining, on-orbit operation, and other scenarios, providing reliable technical support for high-end manufacturing and aerospace missions.
[0018] 2. In this invention, the insulating layer, intermediate layer, base layer, and connecting base plate are all made of flexible materials. The conductive ink and carbon nanotubes in the electrode layer are themselves flexible conductive materials that can be directly printed onto a flexible substrate to adapt to deformation requirements. The electrode layer can also achieve good flexible bending performance through micron-level thinning treatment with copper or silver. This fully flexible material system gives the electrostatic adsorption structure excellent deformation capability, as well as excellent high and low temperature resistance, radiation resistance, and plasma environment adaptability. It can adapt to adsorption surfaces with large surface roughness and curvature. Compared with rigid electrostatic chucks, this invention has a higher adsorption force retention rate on rough surfaces, while the adsorption force of rigid chucks decreases significantly on rough surfaces. This invention exhibits excellent adhesion on surfaces with high curvature, while rigid chucks have poor adhesion on such surfaces. This characteristic significantly expands the application boundaries of electrostatic adsorption technology, especially suitable for complex scenarios such as on-orbit operation of spacecraft and processing of irregularly shaped workpieces.
[0019] 3. The layered structure design of this invention not only optimizes the electric field distribution and improves the adsorption performance, but also effectively reduces the risk of electrode breakdown through the layered insulation design of the flexible insulating layer, flexible intermediate layer, and flexible substrate layer. The breakdown voltage safety factor of this invention is significantly improved compared with the traditional planar structure. At the same time, the flexible electrode layer is prepared by a wet etching process, resulting in good electrode thickness uniformity, avoiding electric field distortion and local breakdown problems caused by uneven electrode thickness, and significantly improving the reliability and service life of the structure. Attached Figure Description
[0020] Figure 1 This is a schematic diagram of the overall structure of the electrostatic adsorption structure with a stacked concentric circle configuration as described in this invention. Figure 2 This is an exploded structural diagram of each component of the electrostatic adsorption structure with a stacked concentric circle configuration as described in this invention. Figure 3 This is a schematic diagram of the concentric ring electrode layer structure in the electrostatic adsorption structure with a stacked concentric circle configuration described in this invention. Figure 4 This is a schematic diagram of the solid circular electrode layer structure in the electrostatic adsorption structure with a stacked concentric circle configuration described in this invention.
[0021] In the attached diagram: 1. Flexible insulating layer; 2. First electrode layer; 3. Flexible intermediate layer; 4. Second electrode layer; 5. Flexible substrate layer; 6. Flexible connecting base plate. Detailed Implementation
[0022] The following is in conjunction with the appendix Figure 1-4 This application will be described in further detail.
[0023] This application discloses an electrostatic adsorption structure based on a stacked concentric circle configuration, such as... Figure 1 and Figure 2 As shown, the structure comprises six layers arranged from bottom to top: a flexible connecting base plate 6, a flexible base layer 5, a second electrode layer 4, a flexible intermediate layer 3, a first electrode layer 2, and a flexible insulating layer 1. Each layer is fixedly connected by hot pressing or bonding. The flexible insulating layer 1 is an adsorption contact surface of an electrostatic adsorption structure.
[0024] In this embodiment, the layered structure design of the present invention not only optimizes the electric field distribution and improves the adsorption performance, but also effectively reduces the risk of electrode breakdown through the layered insulation design of the flexible insulating layer 1, the flexible intermediate layer 3, and the flexible base layer 5. The breakdown voltage safety factor of the present invention is significantly improved compared with the traditional planar structure. At the same time, the flexible electrode layer is prepared by printing process, and the electrode thickness uniformity is good, avoiding electric field distortion and local breakdown problems caused by uneven electrode thickness, thus significantly improving the reliability and service life of the structure.
[0025] like Figure 3 and Figure 4 As shown, Figure 4 The second electrode layer 4 is a solid circular electrode. Figure 3 The first electrode layer 2 is a concentric circular electrode. The first electrode layer 2 and the second electrode layer 4 are respectively connected to excitation voltages of opposite polarities to generate electrostatic adsorption force between the electrostatic adsorption structure and the adsorbed object. Simulation and experimental data show that the optimal ratio of electrode width to spacing of the first electrode layer 2 is 8:7, maximizing the electrostatic adsorption force. This ratio is suitable for most adsorbed objects and application scenarios. Under the same excitation voltage and adsorption area, this ratio allows for a more uniform electric field distribution and higher charge induction efficiency, improving the adsorption force by more than 40% compared to traditional planar structures. While a small electrode spacing can increase the adsorption force, it easily leads to short circuits between electrodes. The 8:7 ratio, while ensuring high adsorption force, reduces the probability of breakdown through reasonable spacing design, ensuring a good safety factor for the structure even at 2.5kV DC voltage. For each fixed electrode spacing, there exists an optimal electrode width that maximizes the adsorption force, and this optimal electrode width varies with the electrode spacing. Specifically, the electrode width of the first electrode layer 2 is 0.3-2mm, and the electrode spacing is 0.15-1.75mm. The electrode width and electrode spacing should be adjusted flexibly according to the actual application conditions, including the type of adsorbed object, the required electrostatic adsorption force, the adsorption surface area, the type of excitation voltage, and the amplitude of the excitation voltage. For example, a smaller electrode size can be selected for lightweight thin-walled parts, while the electrode size can be increased for heavy loads, balancing adsorption force and structural flexibility.
[0026] In this embodiment, the present invention overcomes the performance bottleneck of traditional planar electrostatic adsorption structures by employing a stacked concentric circle electrode configuration and an optimal electrode width-to-width ratio of 8:7. Experimental data shows that, under the same excitation voltage and adsorption area, the average adsorption force of the present invention is significantly improved compared to commercial electrostatic chucks and traditional planar electrostatic adsorption films, and the stability of the adsorption force is also greatly enhanced. This performance breakthrough effectively solves the problems of workpiece displacement and adsorption failure that are prone to occur in traditional structures in precision machining, on-orbit operation, and other scenarios, providing reliable technical support for high-end manufacturing and aerospace missions.
[0027] The first electrode layer 2 and the second electrode layer 4 are respectively connected to excitation voltages of opposite polarities to generate electrostatic adsorption force between the electrostatic adsorption structure and the adsorbed object; wherein, the excitation voltage is of the type of DC, sine wave, square wave or arbitrary waveform.
[0028] Specifically, the flexible insulating layer 1, flexible intermediate layer 3, and flexible base layer 5 are made of polymer film materials such as polyimide (PI), polyethylene terephthalate (PET), polyvinylidene fluoride (PVDF), polyethylene naphthalate (PEN), polyphenylene sulfide (PPS), polycarbonate (PC), polyurethane (PU), parylene (Parylene), silicone plastic, and biaxially oriented polypropylene (BOPP), as well as one or more of PDMS, ECOFLEX0030, and ECOFLEX0050 insulating silicone rubber. The flexible materials such as polyimide (PI) and PDMS possess superior... With its exceptional deformation capability, it adapts to complex surfaces and can readily adapt to adsorption surfaces with large surface roughness or small radius of curvature. Compared with rigid electrostatic chucks, it significantly improves the adsorption force retention rate on rough surfaces. The selected material has wide temperature range adaptability (-196℃ to 150℃), radiation resistance, and plasma environment stability, and can be directly applied to harsh scenarios such as on-orbit operation of spacecraft without additional protective measures. The material's high insulation strength effectively isolates the electrode layer from the external environment, avoiding the risk of leakage. At the same time, the layered insulation design of the flexible insulation layer 1, flexible intermediate layer 3, and flexible base layer 5 further improves the breakdown voltage safety factor of the structure.
[0029] It should be noted that the flexible insulating layer 1, the flexible intermediate layer 3, and the flexible base layer 5 may be made of the same or different materials.
[0030] Specifically, the flexible connecting base plate 6 is made of one or more of polyimide, polyetheretherketone, polytetrafluoroethylene, or silicone rubber, and its compressive strength is <50kPa and elongation at break is >10%, in order to improve the contact between the electrostatic adsorption structure and the target object, thereby enhancing the electrostatic adsorption force. It also has good insulation properties and can adapt to high and low temperature environments, radiation environments, and plasma environments ranging from -196℃ to 150℃. The flexible connecting base plate 6, with its inherent flexibility, can deform with the adsorption surface, maximizing the contact area between the entire adsorption structure and the target object. This flexible fit increases the contact area, thereby improving the magnitude and stability of the adsorption force. The high insulation performance of the flexible connecting base plate 6 protects the internal structure from external electromagnetic interference while providing mechanical support for the entire adsorption structure, meeting both flexibility and structural strength requirements.
[0031] Specifically, the materials of the first electrode layer 2 and the second electrode layer 4 are one or more of copper, silver, conductive ink, or carbon nanotube conductive materials. The high conductivity of the conductive material ensures the adsorption force, while the low resistivity of materials such as copper and silver can reduce the internal resistance loss of the electrode, so that the excitation voltage can be efficiently converted into an electrostatic field, ensuring the maximum output of the adsorption force. Materials such as conductive ink and carbon nanotubes are suitable for flexible printing processes, which can realize high-precision, large-area electrode preparation, and the electrode thickness uniformity is good, avoiding electric field distortion and local breakdown caused by uneven thickness.
[0032] In this embodiment, the insulating layer, intermediate layer, base layer, and connecting base plate of the present invention are all made of flexible materials; the conductive ink and carbon nanotubes of the electrode layer are themselves flexible conductive materials, which can be directly printed on the flexible substrate to adapt to deformation requirements; the electrode layer can also achieve good flexible bending performance through micron-level thinning treatment with copper or silver. This fully flexible material system enables the electrostatic adsorption structure to have excellent deformation capability, as well as excellent high and low temperature resistance, radiation resistance, and plasma environment adaptability, and can adapt to adsorption surfaces with large surface roughness and large surface curvature; compared with rigid electrostatic chucks, the present invention has a higher adsorption force retention rate on rough surfaces, while the adsorption force of rigid chucks attenuates significantly on rough surfaces; the present invention exhibits excellent adhesion on large curvature surfaces, while rigid chucks have poor adhesion on large curvature surfaces. This characteristic significantly expands the application boundaries of electrostatic adsorption technology, especially suitable for complex scenarios such as on-orbit operation of spacecraft and processing of irregularly shaped workpieces.
[0033] Specifically, the thickness of the flexible insulating layer 1 is 5-30 μm, the thickness of the flexible intermediate layer 3 is 10-50 μm, and the thickness of the flexible base layer 5 is 10-100 μm. Under the same conditions, the smaller the thickness of the flexible insulating layer 1 and the flexible intermediate layer 3, the higher the electrostatic field strength and the greater the electrostatic adsorption force, but the easier it is to break down. The thickness range can be flexibly adjusted according to the actual application conditions such as the type of adsorbed object, the required electrostatic adsorption force, the adsorption surface area, the type of excitation voltage, and the amplitude of the excitation voltage. While ensuring the adsorption force, it meets the electrical safety requirements. The synergistic optimization of the layer thickness means that the thickness design of the flexible intermediate layer 3 and the flexible base layer 5 must take into account both structural flexibility and mechanical strength. A thicker flexible intermediate layer 3 can enhance the insulation isolation between electrode layers, while a thicker flexible base layer 5 can improve the tensile strength of the overall structure. The three work together to achieve a balance between flexibility and reliability.
[0034] Specifically, the thickness of the first electrode layer 2 is 5-20 μm, and the thickness of the second electrode layer 4 is 5-20 μm. Excessive electrode thickness will reduce the electric field strength, thereby affecting the adsorption force output. This thickness range ensures the mechanical strength of the electrode while enabling the electric field to act more efficiently on the surface of the adsorbed object, improving the charge induction efficiency and maximizing the electric field strength. The thinner electrode layer has better flexibility and can bend with the deformation of the flexible insulating layer 1. At the same time, it is compatible with the precision requirements of flexible printing process and avoids printing defects caused by excessive electrode thickness.
[0035] The working principle of electrostatic adsorption in this invention is as follows: When the electrostatic adsorption structure is attached to the surface of the target object, the first electrode layer 2 and the second electrode layer 4 are respectively subjected to excitation voltages of opposite polarities, forming an electric field between the flexible insulating layer 1 and the target object. For conductive target objects, the electric field induces charges on their surface; for dielectric target objects, the electric field induces polarized charges on their surface. These charges attract each other with the charges on the surface of the electrostatic adsorption structure, forming an electrostatic adsorption force, thereby achieving adsorption of the target object. In this process, the flexible connecting base plate 6, through its own flexibility, allows the entire adsorption structure to better fit the surface of the target object, increasing the contact area and thus improving the magnitude and stability of the electrostatic adsorption force. Traditional electrostatic adsorption structures usually use a rigid-flexible connecting base plate 6, which cannot effectively adapt to complex target object surfaces, resulting in a small contact area and unstable adsorption force. The flexible connecting base plate 6 of this invention adopts a flexible design, which can adapt to various adsorption surfaces. Combined with the flexibility of the flexible insulating layer 1, it achieves effective adsorption on complex surfaces, while improving the magnitude and stability of the adsorption force. This invention directly adsorbs the target object through the flexible insulating layer 1, the flexible base layer 5 provides insulation support for the electrode layer, and the flexible connecting base plate 6 mainly plays the role of supporting the overall structure, flexible adaptation and environmental protection, providing flexible adaptation capability for the overall structure. The two work together to achieve stable adsorption of the target object.
[0036] The following provides specific examples and experimental results: The flexible insulating layer 1 has a thickness of 10 μm, the flexible intermediate layer 3 has a thickness of 25 μm, the flexible base layer 5 has a thickness of 25 μm, the flexible electrodes in the first electrode layer 2 and the second electrode layer 4 have a thickness of 15 μm, the electrode width in the first electrode layer 2 is 0.4 mm, and the electrode spacing is 0.35 mm; the excitation voltage is DC, and the excitation voltage amplitude is 2.5 kV; the adsorption object is a semiconductor silicon wafer, and the adsorption surface area is the area occupied by a circle with a diameter of 75 mm.
[0037] The improved multilayer electrostatic adsorption structure was compared with a commercial electrostatic chuck and a traditional planar electrostatic adsorption film in terms of electrostatic adsorption force. The results are shown in Table 1. It can be found that the adsorption force of the improved multilayer electrostatic adsorption structure is greater than that of the commercial electrostatic chuck, which in turn is greater than that of the traditional planar electrostatic adsorption film. Furthermore, the adsorption performance stability of the improved multilayer electrostatic adsorption structure is greater than that of the commercial electrostatic chuck, which is also greater than that of the traditional planar electrostatic adsorption film. The electrostatic adsorption force test results are shown in Table 1 below: Table 1 Results of electrostatic adsorption force test
[0038] In summary, the electrostatic adsorption structure based on a stacked concentric circle configuration of the present invention utilizes the principle of electrostatic adsorption to generate electrostatic adsorption force between itself and the target object. It is adaptable to various adsorption surfaces, has a large average adsorption force, and strong adsorption force stability, enabling it to complete the adhesion task on multiple types of surfaces. According to the experimental data in Table 1, the average adsorption force of the present invention reaches 17.19 N, with an adsorption force fluctuation of only 9.48%. Compared with traditional planar electrostatic adsorption films, the average adsorption force of the present invention is increased by more than 40%, and the adsorption force fluctuation is reduced by more than 17%. Compared with commercial electrostatic chucks, the average adsorption force of the present invention is increased by more than 18%, and the adsorption force fluctuation is reduced by more than 14%. Compared with traditional planar electrostatic adsorption films and commercial electrostatic chucks, the present invention has significant performance advantages.
[0039] This invention also provides a specific method for fabricating an electrostatic adsorption structure based on a stacked concentric circle configuration, comprising the following steps: S1: A flexible insulating material (selected from polymer films such as polyimide PI and polyethylene terephthalate PET) is used as the flexible intermediate layer 3, and a laminate with double-sided conductive material is used as the first electrode layer 2 and the second electrode layer 4 (selected from copper, silver, conductive ink or carbon nanotubes, etc.) as the flexible substrate. The three are combined to form a substrate. For high-precision electrode patterns, conductive ink is used for printing, and for large-size structures, copper foil is used for etching. S2: Negative dry films are laminated on both sides of the substrate simultaneously. The upper dry film is irradiated with ultraviolet light through a concentric circle mask pattern with an electrode width to spacing ratio of 8:7 and the lower dry film is irradiated with a solid circle mask pattern. The dry film in the irradiated area hardens to form an insoluble resist layer. S3: Use a developer to remove the dry film from the unexposed areas, and then use an etchant to etch away the copper layer that is not protected by the dry film, thereby forming the designed electrode pattern. S4: Use 3% NaOH sodium hydroxide solution to peel off the residual hardened dry film, exposing the completed flexible circuit, to obtain the upper concentric circle first electrode layer 2 and the lower solid circle second electrode layer 4. S5: Under hot pressing conditions of 180℃ and 2.5MPa, the two cover layers, flexible insulating layer 1 and flexible base layer 5, are laminated to both sides of the etched substrate for 3 hours to ensure a tight bond between the cover layer and the electrode layer and to eliminate interlayer bubbles. Each cover layer also includes a thermal adhesive layer. S6: The prepared structure is attached to the flexible connecting base plate 6, and the first electrode layer 2 and the second electrode layer 4 are connected to excitation voltages of opposite polarities respectively. The vertical stacking design of concentric circular electrodes and solid circular electrodes forms a longitudinal electric field superposition, which enhances the adsorption force and obtains an electrostatic adsorption structure based on the stacked concentric circular configuration.
[0040] In summary, this invention maximizes electrostatic adsorption force and stability through an optimal 8:7 width-to-spacing ratio, highly conductive electrode materials, and a thin, flexible insulating layer 1. By employing a reasonable spacing range, layered insulation design, and the selection of highly insulating materials, it reduces the risks of electrode breakdown and leakage. Furthermore, the flexible material system and adjustable parameter range enable adaptation to complex surfaces and extreme environments, expanding the boundaries of technological applications. This multi-dimensional collaborative design allows the invention to maintain high adsorption force and stability while possessing adaptability to complex scenarios not found in traditional electrostatic adsorption structures, providing a novel technical solution for fields such as spacecraft on-orbit operation and semiconductor precision manufacturing.
[0041] The above are all preferred embodiments of this application, and are not intended to limit the scope of protection of this application. Therefore, all equivalent changes made in accordance with the structure, shape and principle of this application should be covered within the scope of protection of this application.
Claims
1. An electrostatic adsorption structure based on a stacked concentric circle configuration, comprising, from bottom to top, a flexible connecting base plate (6), a flexible base layer (5), a second electrode layer (4), a flexible intermediate layer (3), a first electrode layer (2), and a flexible insulating layer (1), wherein each layer is fixedly connected by hot pressing or bonding, and the flexible insulating layer (1) serves as the adsorption contact surface of the electrostatic adsorption structure; wherein: The second electrode layer (4) is a solid circular electrode, and the first electrode layer (2) is a concentric circular electrode. The first electrode layer (2) and the second electrode layer (4) are stacked along the normal of the adsorption contact surface and are respectively connected to excitation voltages of opposite polarities. The vertical stacking design of the concentric circular electrode and the solid circular electrode forms a longitudinal electric field superposition, so that the electrostatic adsorption structure and the adsorbed object generate electrostatic adsorption force. The electrostatic adsorption structure adapts to complex adsorption surfaces with large surface roughness and / or large curvature through its fully flexible structure, and improves the electrostatic adsorption force based on the combination of the stacked concentric circle configuration and the 8:7 electrode width-to-spacing ratio. The electrode width of the first electrode layer (2) is 0.3-2 mm and the electrode spacing is 0.15-1.75 mm. The thickness of the flexible insulating layer (1) is 10 μm, the thickness of the flexible intermediate layer (3) is 25 μm, the thickness of the flexible base layer (5) is 25 μm, and the thickness of the first electrode layer (2) and the second electrode layer (4) is 15 μm. The flexible connecting base plate (6) has a compressive strength of <50kPa and an elongation at break of >10%, so as to deform with the surface of the adsorbed object and increase the contact area between the electrostatic adsorption structure and the adsorbed object.
2. The electrostatic adsorption structure based on a stacked concentric circle configuration according to claim 1, characterized in that: The flexible insulating layer (1), flexible intermediate layer (3), and flexible base layer (5) are made of one or more of the following: polyimide (PI), polyethylene terephthalate (PET), polyvinylidene fluoride (PVDF), polyethylene naphthalate (PEN), polyphenylene sulfide (PPS), polycarbonate (PC), polyurethane (PU), parylene (Parylene), silicone, biaxially oriented polypropylene (BOPP) film, PDMS, ECOFLEX0030, and ECOFLEX0050 insulating silicone rubber.
3. The electrostatic adsorption structure based on a stacked concentric circle configuration according to claim 1, characterized in that: The materials of the first electrode layer (2) and the second electrode layer (4) are one or more of copper, silver, conductive ink or carbon nanotube conductor materials.
4. The electrostatic adsorption structure based on a stacked concentric circle configuration according to claim 1, characterized in that: The flexible connecting base plate (6) is made of one or more of polyimide, polyether ether ketone, polytetrafluoroethylene or silicone rubber. The flexible connecting base plate (6) has a compressive strength of <50kPa and an elongation at break of >10% to improve the contact between the electrostatic adsorption structure and the target object, thereby enhancing the electrostatic adsorption force. It also has good insulation properties and is suitable for high and low temperature, radiation and plasma environments.
5. The electrostatic adsorption structure based on a stacked concentric circle configuration according to claim 1, characterized in that: The excitation voltage can be any one of DC, sine wave, or square wave.
6. The method for fabricating an electrostatic adsorption structure based on a stacked concentric circle configuration according to any one of claims 1-5, characterized in that: Includes the following steps: S1: A flexible substrate is formed by using a flexible insulating material as a flexible intermediate layer (3), a laminate with double-sided conductive material as a first electrode layer (2) and a second electrode layer (4); S2: Negative dry films are laminated on both sides of the substrate simultaneously. The upper dry film is irradiated with ultraviolet light through a concentric circle mask pattern with an electrode width to spacing ratio of 8:7 and the lower dry film is irradiated with a solid circle mask pattern. The dry film in the irradiated area hardens to form an insoluble resist layer. S3: Use a developer to remove the dry film from the unexposed areas, and then use an etchant to etch away the copper layer that is not protected by the dry film, thereby forming the designed electrode pattern. S4: Use 3% NaOH sodium hydroxide solution to peel off the remaining hardened dry film, exposing the completed flexible circuit, and obtain the upper concentric circle first electrode layer (2) and the lower solid circle second electrode layer (4). S5: Under hot pressing conditions of 150-200℃ and 2.0-3.0MPa, the two cover layers, flexible insulating layer (1) and flexible base layer (5), are laminated to both sides of the etched substrate for 2-4 hours to ensure the tight bonding between the cover layer and the electrode layer and to eliminate interlayer bubbles. Each cover layer also includes a thermal adhesive layer. S6: The prepared structure is attached to the flexible connecting base plate (6), and the first electrode layer (2) and the second electrode layer (4) are connected to excitation voltages of opposite polarities respectively. The vertical stacking design of concentric circle electrodes and solid circle electrodes forms a longitudinal electric field superposition, which enhances the adsorption force and obtains an electrostatic adsorption structure based on the stacked concentric circle configuration.
Citation Information
Patent Citations
Adhesive film composite electrostatic adsorption device for non-sensitive attachment tasks
CN116945720B
Adhesive film combined type electrostatic adsorption device for non-inductive attachment task
CN116945720A
Bipolar Electrostatic Chuck
US20070223173A1
KR20220076381A
